Nilai-nilai moral Pada Novel "Orang Miskin Dilarang Sekolah" Karya Wiwid Prasetyo dan Implikasinya terhadap Pembelajaran Bahasa dan Sastra Indonesia di Sekolah - Permanasari, Dian (Lentera: Jurnal Ilmiah Kependidikan, 2017)
The result of the structure analysis are coherent and logical because every element are related. Struggle of the main character to help his friends in school is a major theme in the story. The characterizations according to the function as protagonist and antagonist were articulated and make the story. Vivid progressive plot desain by using the sequence and causality relationship make the reader easier in understanding the storyline. Description of the background further strengthen the plot and characterization. Description of the social background display state at the time. The use of first-person perspective makes the reader feel as if directlyinvolved in the story. Style of language used increasingly beautify the course of the story, attract more the readerâs attention. Background of Javanese society in the story related to moral values, which are the moral values to one self, the moral values to other people, and the moral values to God, reflected by the charactersso it looks that the author wants to show the principle of Java in his work. Analysis of Orang Miskin Dilarang Sekolah novel can fulfill the main competence of curriculum. Structure analysis of the novel can increase studentâs knowledge of how to analyze the structure of novel and improve their language skill.